Evaluation of BTLA (CD272) Immune Checkpoint Levels Related to Hepatitis B virus Infection in Diabetes Mellitus Patients - Al-Hamdani, Baneen abdul Hadi; Al-Mayah, Saif Jabbar Yasir (Medical Science Journal for Advance Research, 2024)
Background: Diabetes mellitus is a persistent disorder characterized by an imbalance in the regulation of glucose levels in the body. Hepatitis B is a hepatotropic virus that may trigger viral hepatitis, cirrhosis, and hepatocellular carcinoma. The B and T lymphocyte attenuator (BTLA/CD272) is a co-inhibitory receptor present in T lymphocytes and B lymphocytes. It plays a crucial role in controlling the activation of lymphocytes during periods of inflammation and infection. BTLA has high levels of expression in T-cells that are particular to the virus, resulting in a strong inhibitory impact on processes such as T-cell proliferation and cytokine release. Objective: The study aims to assess BTLA levels in relation to HBV infection in diabetes mellitus patients. Subjects and methods: A cross-sectional study was conducted from July to October 2023. The serum was obtained from 200 diabetics. All of the patients were tested using an ELISA technique for BTLA and HBc IgG. They were tested using a five-panel kit for HBsAb, HBsAg, HBcAb, HBeAg, and HBeAb. The statistical analysis approach was conducted using SPSS version 26. Results: Serum BTLA levels were correlated with serum HBc IgG positivity (P = 0.043) and total HBc Ab positivity (P = 0.017). There was no correlation between BTLA levels and serum HBs Ab (P = 0.151) or HBe Ab (p = 0.941). BTLA levels were not correlated with diabetes mellitus (P = 0.786). Conclusions: Elevated levels of BTlA in diabetic individuals who are exposed to the hepatitis B virus compared to those without this virus.